Differential effect of valproate and its Delta(2)- and Delta(4)-unsaturated metabolites, on the beta-oxidation rate of long-chain and medium-chain fatty acids - Silva, MFB (2015)
Overall fatty acid oxidation rates were investigated in rat hepatocytes using [9,10-H-3]palmitic, [9,10-H-3]-oleic, [9.10-H-3]-myristic and [2,3-H-3]-phenylpropionic acids. The effect of both valproate (VPA) (0-10 mM) and two of its unsaturated metabolite